2020
DOI: 10.2147/ott.s254118
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of Vitamin K3 Combined with UVB on the Proliferation and Apoptosis of Cutaneous Squamous Cell Carcinoma A431 Cells [Corrigendum]</p>

Abstract: OncoTargets and Therapy is an international, peer-reviewed, open access journal focusing on the pathological basis of all cancers, potential targets for therapy and treatment protocols employed to improve the management of cancer patients. The journal also focuses on the impact of management programs and new therapeutic agents and protocols on patient perspectives such as quality of life, adherence and satisfaction. The manuscript management system is completely online and includes a very quick and fair peer-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This combination treatment potentiated the rate of mitochondrial apoptosis by increased ROS production and MMP depolarization. These findings were further supported by the in vivo experiment 73 …”
Section: Chemosensitizing Mechanism Of Vitamin Ksupporting
confidence: 70%
See 2 more Smart Citations
“…This combination treatment potentiated the rate of mitochondrial apoptosis by increased ROS production and MMP depolarization. These findings were further supported by the in vivo experiment 73 …”
Section: Chemosensitizing Mechanism Of Vitamin Ksupporting
confidence: 70%
“…A pile of literature suggested that parallel to promising anticancer activity of vitamin K3, it has also a strong potential to act as a chemosensitizer for multiple drug‐resistant neoplasms such as colon 26 62 and HTC116 63 cell lines of colon cancer; AN3CA 64,65 cell line of uterine cancer; DU145, 66–68 PC3, 69–71 and LNCaP 71 cell lines of prostate cancer; UC and UMUC‐14 72 cell lines of urothelial cancer; A431 73 cells line of epidermoid carcinoma; 253JB‐V,T24 72,74–77 and RT4 77,78 cell lines of bladder cancer; KB‐V1 79 cell line of cervix carcinoma; MDA‐MB 231 63 and MCF‐7 62,64,71,79–84 cell lines of breast cancer; A172 71 and U87MG 63 cell lines of glioblastoma; CG1 85 cell line of nasopharyngeal carcinoma; MOLT‐4, 86 K562, 87,88 HL‐60, 89 Jurkat, 62,63,90–92 , and CCRF‐CEM, K562 90,63 cell lines of leukemia; TLT 93 and HepG2 82 cell lines of HCC; HeLa 94 cell line of human cervical adenocarcinoma; MRC‐5 82 A549 94,95 and HCT116 96 cell lines of human colorectal carcinoma; RCC and ACHN 82,97 cell lines of renal carcinoma; KB, 64 HSC‐2, HSC‐3, and HGF 89 cell lines of human oral squamous cell carcinoma; MDAH 2774 98 and NCI/ADR‐RES 83 cell lines of ovarian carcinoma; and PANC1 71 cell line of human pancreatic cancer as given in Table 3.…”
Section: Chemosensitizing Mechanism Of Vitamin Kmentioning
confidence: 99%
See 1 more Smart Citation